2015
DOI: 10.1098/rspb.2015.0124
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of risk-sensitive behaviour of prey following disease-induced decline of an apex predator, the Tasmanian devil

Abstract: Apex predators structure ecosystems through lethal and non-lethal interactions with prey, and their global decline is causing loss of ecological function. Behavioural changes of prey are some of the most rapid responses to predator decline and may act as an early indicator of cascading effects. The Tasmanian devil ( Sarcophilus harrisii ), an apex predator, is undergoing progressive and extensive population decline, of more than 90% in long-diseased areas, caused by a novel disease. Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…GUDs at one study site on Maria Island appeared to deviate from the Figure 2. (a) Effects plot from the best-supported LMM investigating possum GUDs before and after the introduction of devils to Maria Island. This demonstrates that GUDs were indistinguishable between the two regions in the 'before' period (Hollings et al 2015), however following the introduction of devils to Maria Island, GUDs were significantly higher on Maria Island than the control region. The solid dots represent the model fit and the transparent dots show the raw data.…”
Section: Possum Guds Were Initially Indistinguishable Between Mariamentioning
confidence: 80%
See 2 more Smart Citations
“…GUDs at one study site on Maria Island appeared to deviate from the Figure 2. (a) Effects plot from the best-supported LMM investigating possum GUDs before and after the introduction of devils to Maria Island. This demonstrates that GUDs were indistinguishable between the two regions in the 'before' period (Hollings et al 2015), however following the introduction of devils to Maria Island, GUDs were significantly higher on Maria Island than the control region. The solid dots represent the model fit and the transparent dots show the raw data.…”
Section: Possum Guds Were Initially Indistinguishable Between Mariamentioning
confidence: 80%
“…Analysis during the 'before' period indicated that non-target species rarely took more than 15% of the food and never more than 25% (Hollings et al 2015). Analysis during the 'before' period indicated that non-target species rarely took more than 15% of the food and never more than 25% (Hollings et al 2015).…”
Section: Giving-up Density Experimentsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is costly for an organism to respond to predators that are extinct, therefore we should expect behavioural changes among prey to be rapid in the absence of predation (Lahti et al., ). After all, it is not in an animal's best interest to be overly cautious in environments under decreasing predator threat (Hollings et al., ). This assumption may partly explain why some prey responses to new predators are often learned during their development (Blumstein et al., ; Anson & Dickman, ; Carthey & Banks, ; Tortosa et al., ).…”
Section: Neurobiological Mechanisms Underlying Prey Responsesmentioning
confidence: 99%
“…Wallabies also responded to the introduction of devils to Maria Island by increasing activity at periods of the day when devils are inactive (Cunningham et al ). Because possums are typically arboreal but often forage on the ground, the trends we show here could reflect changes in abundance or increased ground‐based activity by possums in response to a relaxed landscape of fear (Hollings et al ; Cunningham et al ).…”
Section: Discussionmentioning
confidence: 84%